KECERDASAN BUATAN DAN PERLINDUNGAN DATA: ANALISIS REGULASI YANG ADIL UNTUK SISTEM HUKUM INDONESIA - Sri Wulandari, Yudha (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The development of artificial intelligence (AI) has had a significant impact on various aspects of life, including legal systems and data protection. This study aims to analyze policies and regulations related to AI and data protection in Indonesia, by comparing them with international standards. The method used in this research is a normative approach through the analysis of legislation, case studies, and literature review. The results show that AI regulation in Indonesia is still in its early stages, with several key challenges related to ethics, security, and privacy rights. Therefore, strategic steps are needed in the formulation of policies that are more adaptive and based on the principles of justice and legal certainty. The findings indicate that current AI regulations in Indonesia are not yet fully prepared to address the challenges posed by rapid technological advancements. Key issues include ethical concerns, data security, and privacy rights, which are often overlooked. Hence, strategic actions are necessary to develop more adaptive, transparent policies based on the principles of justice and legal certainty. This study also highlights the need for regulatory updates that balance technological innovation with the protection of individual rights, so that Indonesia can fully harness the potential of AI without compromising privacy and data security.